Spiritual Communication in Mental Resilience: An Autoethnographic Reflection of a Soldier at Disbintalad Jakarta - Fadhil Muhammad; Ellys Lestari Pambayun; Ira Purwitasari (STAI Publisistik Thawalib Jakarta, 2026)
The high psychological burden experienced by Indonesian Army personnel necessitates strengthening mental resilience. However, limited research has explored the role of spiritual communication in fostering soldiers’ psychological resilience through direct and reflective experiences. This study aims to analyze spiritual communication, interaction patterns, communication symbols, and spiritual meanings in strengthening soldiers’ mental resilience. A qualitative approach with an autoethnographic design was employed. Data were collected through participant observation, in-depth interviews, document analysis, and reflective journals. Data analysis involved data condensation, data presentation, conclusion drawing, and verification through triangulation and researcher reflexivity. The findings indicate that soldiers’ spiritual communication develops through four stages: initiation, internalization, expression, and transcendence. Communication patterns occur vertically between spiritual mentors and soldiers and horizontally through peer support among soldiers. Spiritual communication symbols appear in verbal, nonverbal, and ritual forms, integrating religious values, national ideology, and military culture. Spirituality is understood as a source of strength, a moral compass, a bond of solidarity, and a pathway to inner peace. Furthermore, interactive, ritualistic, and intrapersonal spiritual communication serves as a critical reflective mechanism for renegotiating mental resilience in the face of occupational pressures and military challenges. The study concludes that spiritual communication plays a significant role in strengthening soldiers’ mental resilience through meaning-making, solidarity, reflection, and inner peace. This research contributes to the development of studies in spiritual communication and military psychology while offering a humanistic perspective through an autoethnographic approach.